2016
DOI: 10.1097/mca.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of microcirculation after primary percutaneous intervention in ST-segment elevation myocardial infarction

Abstract: ObjectivesA pathophysiological mechanism of microvascular dysfunction in ST-segment elevation myocardial infarction (STEMI) is multifactorial; thus, multiple modalities were needed to precisely evaluate a microcirculation.MethodsWe complementarily assessed microcirculation in STEMI by the index of microcirculatory resistance (IMR) and coronary flow reserve (CFR) immediately after a primary percutaneous intervention in 89 STEMI patients. Cardiovascular and cerebrovascular events (MACCE) including cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
4
16
1
Order By: Relevance
“…13 The combination of an increased IMR and reduced CFR has been associated with enhanced detection of microvascular obstruction 18 and viability and prognosis. 16 However, in that study, only 10 major adverse cardiac and cerebrovascular events occurred, of which 5 were revascularizations. Changes in IMR and CFR within 24 hours after reperfusion have been associated with LV ejection fraction (LVEF).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…13 The combination of an increased IMR and reduced CFR has been associated with enhanced detection of microvascular obstruction 18 and viability and prognosis. 16 However, in that study, only 10 major adverse cardiac and cerebrovascular events occurred, of which 5 were revascularizations. Changes in IMR and CFR within 24 hours after reperfusion have been associated with LV ejection fraction (LVEF).…”
mentioning
confidence: 77%
“…14 CFR is associated with composite cardiovascular outcomes, including revascularization, in patients with stable coronary disease 15 and after acute STEMI. 16 We have recently shown that IMR is more closely associated with severe microvascular pathology, LV remodeling, and health outcome than either the angiogram or CFR, 17 but whether the combination of IMR and CFR adds prognostic value is uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of six studies, a median IMR > 40 was an independent predictor of death [20]. In some studies, the combination of a high IMR and reduced CFR enhances the detection of microvascular obstruction, but in other studies, the combination did not have any prognostic value [21,22].…”
Section: Coronary Flow Reserve and The Index Of Microvascular Resistancementioning
confidence: 99%
“…5,6 In this case report, we presented the results from the comprehensive physiologic assessment in culprit vessel after primary PCI in STEMI patients and validated the results using cardiac MR findings. There is acute and overt inflammatory change in myocardial cell and vasculature, especially in acute phase of myocardial infarction.…”
Section: Casementioning
confidence: 99%